Preparation of Nano Niosomes Loaded with Rutin and Aloe Gel Extract - Thi Hai Yen, Tran; Thi Hien, Hoang; Thi Thu Giang, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
Rutin is a natural flavonoid that has many effects on human health and beauty. However, rutin has low solubility and bioavailability. Niosomes are drug delivery system that enhance drug permeation of drug through the skin. Aloe is widly used in cosmetic preparations due to its anti-aging, moisturizing and essential skin nutrients. Therefore, the aim of study is preparation of nano niosomes, loaded with rutin and aloe gel extraction (rutin-aloe niosomes) by thin film hydration method. Rutin niosomes was reduced size by ultrasonic method. The size and distribution of vesicles were determined by dynamic light scattering method.  Drug content in niosomal suspension was determined by UV-Vis absorption spectroscopy. The results showed that rutin-aloe niosomes were prepared by thin-film hydration method using Span 60, cholesterol and rutin in molar ratio of 7:3:4 using aloe gel extract as hydration solvent. Mixture of methanol-chloroform (volume ratio 1:1) was used as solvent for solution of membrane companents for evaporation. The manufactured rutin-aloe niosomes had size of about 160 nm, the entrapment efficiency was 95,57% and drug loading was 32,06%. Keywords Rutin, aloe, niosomes, nano, entrapment efficiency, drug loading. References [1] A. Ganeshpurkar, A.K. Saluja, The Pharmacological Potential of Rutin, Saudi pharmaceutical journal 2 (2017) 149-164. https://doi.org/10.1016/j.jsps.2016.04.025. [2] N.B. Mahale, P.D. Thakkar, Niosomes: novel sustained release nonionic stable vesicular systems—an overview, Advances in colloid and interface science 183 (2012) 46-54. https://doi.org/10.1016/j.cis.2012.08.002 [3] V.B. Junyaprasert, P. Singhsa, Physicochemical properties and skin permeation of Span 60/Tween 60 niosomes of ellagic acid, International journal of pharmaceutics 2 (2012) 303-311. https://doi.org/10.1016/j.ijpharm.2011.11.032. [4] A. Manosroi, P. Jantrawut et al, In vitro and in vivo skin anti-aging evaluation of gel containing niosomes loaded with a semi-purified fraction containing gallic acid from Terminalia chebula galls, Pharmaceutical biology 11 (2011) 1190-1203. https://doi.org/10.3109/13880209.2011.576347. [5] A. Surjushe, R. Vasani et al, Aloe vera: a short review, Indian journal of dermatology 4 (2008) 163 - 166. https://doi.org/10.4103/0019-5154.44785. [6] M. Takahashi, D. Kitamoto et al, Liposomes encapsulating Aloe vera leaf gel extract significantly enhance proliferation and collagen synthesis in human skin cell lines, Journal of oleo science 12 (2009) 643-650. https://doi.org/ 10.5650/jos.58.643.